The effects of liraglutide and metformin treatment on fracture healing in partially insulinopenic diabetic rats - Turhan, Banu; Sağlam, Sönmez; Yücel, Mücahit Osman; Dalaslan, Raşit Emin; Sungur, Mehmet Ali; Demir, Fatih; Karaduman, Zekeriya Okan; Arıcan, Mehmet (Frontiers in Endocrinology, 2025)
PurposeAlthough Metformin has been studied, the comparative or synergistic effect with GLP-1 agonists like Liraglutide on fracture healing remains poorly characterized. This study aimed to evaluate the impact of metformin, liraglutide, and their combination on fracture healing in a rat model of partially insulinopenic diabetes mellitus (DM).MethodsSixty male Wistar rats (10–14 weeks old, 350 ± 50g) were divided into five groups of twelve rats each: Control, DM, Met (Metformin), L (Liraglutide), and Met+L. Partially insulinopenic DM was induced in all experimental rats except the control group using streptozotocin (STZ) and nicotinamide (NA) combination. A femoral fracture was created, and a Kirschner wire was inserted retrogradely into the femoral canal. Liraglutide was injected subcutaneously at a daily dose of 0.6 mg/kg into the rats in the L and Met+L groups, and oral metformin was administered to the rats in the Met and Met+L groups daily at a dose of 180 mg/kg. On the 15th, 30th, and 45th days, four rats from each group were selected randomly and euthanized, and the femurs were examined radiographically, biomechanically, and histopathologically.ResultsThe baseline characteristics of the rats before the study showed no significant differences between the groups (p>0.05). Biomechanical test results showed a significant main effect of group (p<0.001), indicating that overall Newton values varied across groups. Additionally, a significant main effect of experimental day was found (p<0.001), suggesting that Newton values changed across days regardless of group. Histopathological scores showed a statistically significant difference between the groups on the 15th day, with the L group having 75% scoring 7 (p=0.047), and on the 45th day, with the L and Met+L groups both having 75% scoring 9 (p=0.036). Conversely, no significant difference was found in radiological scores between the groups on the 15th day (p=0.934), 30th day (p=0.649), and 45th day (p=0.502) of the experiment.ConclusionBoth metformin and liraglutide improve fracture healing in a partially insulinopenic diabetic rat model, and these findings suggest that liraglutide may offer a superior therapeutic advantage over metformin in accelerating fracture repair in patients with diabetes.